Arbuscular mycorrhizal fungi alleviate abiotic stresses in potato plants caused by low phosphorus and deficit irrigation/partial root-zone drying. (5th February 2018) - Liu, Caixia; Ravnskov, Sabine; Liu, Fulai; Rubæk, Gitte H.; Andersen, Mathias N.
Abstract: Deficit irrigation (DI) improves water use efficiency (WUE), but the reduced water input often limits plant growth and nutrient uptake. The current study examined whether arbuscular mycorrhizal fungi (AMF) could alleviate abiotic stress caused by low phosphorus (P) fertilization and DI. A greenhouse experiment was conducted with potato grown with (P1) or without (P0) P fertilization, with AMF (M1+: Rhizophagus irregularis or M2+: Glomus proliferum ) or AMF-free control (M−) and subjected to full irrigation (FI), DI or partial root-zone drying (PRD). Inoculation of M1+ and M2+ maintained or improved plant growth and P/nitrogen (N) uptake when subjected to DI/PRD and P0. However, the positive responses to AMF varied with P level and irrigation regime. Functional differences were found in ability of AMF species alleviating plant stress. The largest positive plant biomass response to M1+ and M2+ was found under FI, both at P1 and P0 (25% increase), while plant biomass response to M1+ and M2+ under DI/PRD (14% increase) was significantly smaller. The large growth response to AMF inoculation, particularly under FI, may relate to greater photosynthetic capacity and leaf area, probably caused by stimulation of plant P/N uptake and carbon partitioning toward roots and tubers. However, plant growth response to AMF was not related to the percentage of AMF root colonization. Arbuscular mycorrhizal fungi can maintain and improve P/N uptake, WUE and growth of plants both at high/low P levels and under FI/DI. If this is also the case under field conditions, it should be implemented for sustainable potato production.